Sex bias in parasitism by Deladenus siricidicola and its implications for the success of biological control of invasive Sirex noctilio populations - Falconaro, Antonella Carla; Fischbein, Deborah; Corley, Juan Carlos (Taylor and Francis, 2025)
In systems with an arthropod host and a parasite, there is no general pattern in the sex bias in the infection. One of the best-studied forest pest systems involves the woodwasp pest Sirex noctilio (Hymenoptera: Siricidae) and its biological control agent, the nematode Deladenus ( = Beddingia) siricidicola, which infects female wasps. Until now, a sexual bias in the infection had not been considered when the nematode was introduced into wasp-infested plantations. In the studied populations in Patagonia, both male and female wasps were equally infected. We discuss the potential implications of these findings for the success of biological control programmes.